Indonesia According to Sam Ratulangie: a Contribution of thoughts from Minahasa to Indonesia - Rogahang, Steven S. N. (Indonesian Journal of Business Analytics, 2024)
This article departs from the central issue that Indonesia is currently again faced with the issue of religious radicalism and ethnic sentiment. The roots of the Pancasila ideology, namely nationalism, religion and communism, which are the basic values ​​of the nation's ideology and philosophy, are starting to be opposed to one another. Religious people once again put forward the issue of communism as the source of the nation's problems. Meanwhile, lay people and academics tend to see the politicization of religion in it. This also had an impact on national-local ideological turmoil. The assumption that Pancasila is not yet fully understood and fully supported at the local level, so it is full of conflicts and interests, makes the author interested in raising this title. Minahasa, as part of Indonesia which has a Christian majority, feels that it has contributed to the process of becoming Indonesian. Using a descriptive-analytical method, this article aims to describe the ideas of Sam Ratulangie - thinker, fighter and futurologist from Minahasa - about being Indonesian, then analyze them to obtain the contribution of Minahasa ideas and thoughts to Indonesia. This article ultimately concludes that Minahasa plays a very important role in the process of becoming Indonesian.